2015
DOI: 10.1007/s11105-015-0932-4
|View full text |Cite
|
Sign up to set email alerts
|

CC-NBS-LRR-Type R Proteins for Rice Blast Commonly Interact with Specific WRKY Transcription Factors

Abstract: Rice blast resistance caused by Resistance (R) genes, most of which encode coiled-coil (CC), nucleotidebinding (NB), and leucine-rich-repeat (LRR) domains, is race-specific. Panicle blast 1 (Pb1) is a panicle blast resistance gene that confers a durable non-race-specific blast resistance to rice. Despite being non-R, Pb1 also encodes a CC-NB-LRR protein. Pb1 specifically interacts with rice WRKY45, a transcription factor (TF) in the rice salicylic acid signaling pathway, through its CC domain, and that this in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 23 publications
0
19
0
Order By: Relevance
“…Next, we identified 74 candidate genes in the LAFBR regions and obtained their annotation information (Additional file 3 : Table S3). None of them are homologous to any known NBS-type R gene family in the rice genome (Liu et al 2015 ; Liebranda et al 2013 ; Hu et al 2005 ) (Additional file 3 : Table S3). We classified those candidate genes into nine gene families based on the gene annotation information: 1) 20.3 % (15 of 74) belong to the receptor-like protein kinase gene family; 2) 16.2 % (12 of 74) are transcription factor genes; 3) 12.2 % (9 of 74) are ubiquitin-related genes; 4) 12.2 % (9 of 74) are phosphorylation-related genes; 5) 10.8 % (8 of 74) are DNA/ATP-binding genes; 6) 8.1 % (6 of 74) are oxidase/oxidoreductase genes; 7) 5.4 % (4 of 74) are heat shock protein genes; 8) 4.1 % (3 of 74) are LRR type genes; and 9) 10.8 % (8 of 74) are other defence related genes (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Next, we identified 74 candidate genes in the LAFBR regions and obtained their annotation information (Additional file 3 : Table S3). None of them are homologous to any known NBS-type R gene family in the rice genome (Liu et al 2015 ; Liebranda et al 2013 ; Hu et al 2005 ) (Additional file 3 : Table S3). We classified those candidate genes into nine gene families based on the gene annotation information: 1) 20.3 % (15 of 74) belong to the receptor-like protein kinase gene family; 2) 16.2 % (12 of 74) are transcription factor genes; 3) 12.2 % (9 of 74) are ubiquitin-related genes; 4) 12.2 % (9 of 74) are phosphorylation-related genes; 5) 10.8 % (8 of 74) are DNA/ATP-binding genes; 6) 8.1 % (6 of 74) are oxidase/oxidoreductase genes; 7) 5.4 % (4 of 74) are heat shock protein genes; 8) 4.1 % (3 of 74) are LRR type genes; and 9) 10.8 % (8 of 74) are other defence related genes (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The gene expression analysis following the inoculation with Botrytis cinerea through microarray revealed the differential expression of WRKY TFs within 18 h of pathogen infection (Windram et al, 2012 ). In one study, Liu et al ( 2016 ) reported the increased expression of WRKY6 gene in the Solanum pimpinellifolium cultivar L3708 after the plants found infection with Phytophthora infestans and Botrytis cinerea or get exposed to other abiotic stress. Similarly, the increased resistance against downy mildew pathogen was demonstrated in five transgenic broccoli lines over-expressing BoWRKY6 (Jiang et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…The conserved motifs and slightly varied WRKY domain play crucial role in mediating complex functional protein-protein interaction observed between different WRKY members or those reported for WRKYs with other regulatory protein partners through both auto regulation or may involve cross regulatory mechanisms (Chi et al, 2013 ; Agarwal et al, 2014 ). The cross-regulatory pathway for their regulatory mechanism may involve several interacting proteins such as DNA binding proteins and other components including MAP kinases (Ishihama and Yoshioka, 2012 ), calmodulin (Park et al, 2005 ), VQ proteins (Chi et al, 2013 ), histone deacetylases (Glatt et al, 2011 ), E3 ubiquitin ligases (Miao and Zentgraf, 2010 ), and CC-NBS-LRR type R-proteins (Liu et al, 2016 ). The autoregulatory control mechanism could occur through negative feedback loop and direct binding of the pathogen associated molecular pattern (PAMP) induced WRKY genes and other expressed target genes.…”
Section: Introductionmentioning
confidence: 99%
“…Pb1 transcript levels have increased during the development of Pb1-resistant varieties and effectively control panicle blast [58]. Pb1-mediated resistance seems to be mediated by a signaling pathway distinct from that involving typical NBS-LRR proteins [59].…”
Section: Map-based Cloning Of Other Qtls For Race-nonspecific Resistancementioning
confidence: 99%